Evaluation of physical and vital signs and the effect of carnosine in experimental hyperthyroidism - Cevat Yazıcı; Gönül Şeyda Seydel; Inayet Gunturk; Fatma Dağlı (Cukurova Medical Journal, 2022)
Purpose: This study aims to investigate the effects of experimental hyperthyroidism and carnosine which is known to have antioxidant properties on physical and vital findings in rats, and to determine the relationship between these parameters and free T3 (FT3) levels. Materials and Methods: Rats were analyzed in 7 groups (each containing 12 animals); control (CONT), hyperthyroidism-1 (T:10-day L-thyroxine (L-T4) administration), hyperthyroidism-2 (T-T: 20-day L-T4 administration), Carnosine (10 day carnosine administration), Hyperthyroidism-1 + Carnosine (T-C), Hyperthyroidism-2 + Carnosine (T-TC), and Carnosine + Hyperthyroidism-1 (C-T). In order to create a hyperthyroidism model, L-thyroxine (L-T4) doses of 300 µg/kg rat weight/day and carnosine doses of 300 µg/kg rat weight/ day were intraperitoneally (ip) administered to the rats. Results: After 10 and 20 days of thyroxine administration, FT3 levels (T:3.640.51pg/mL, T-T: 4.060.91pg/mL) and body temperature (T:37.10.3oC, T-T: 37.60.3oC), significantly increased while body weight decreased (T:240.722.0g, T-T:263.028.7g). Carnosine administration only prevented the increase of FT3 levels, but had no effect on other parameters. Conclusion: The increased FT3 levels observed with L-T4 administration were consistent with the physical and vital findings, but carnosine administration did not reflect the expected effects on the physical findings observed in the hyperthyroid condition.